Short-Term Oral Administration of 1.5 μg/kg bw/day of Deoxynivalenol Significantly Exacerbates Inflammatory and Itching Symptoms in a Mouse Model of Imiquimod-Induced Psoriasis - Takayoshi Miyamoto; Mariko Komuro; Ryota Aihara; Chiharu Ohira; Mao Kaneki; Naoki Iwashita; Yoshiichi Takagi; Atsushi Miyasaka; Masayo Kushiro; Shiro Miyake; Tomoki Fukuyama (Toxins)
Deoxynivalenol (DON) is a mycotoxin commonly found worldwide and is implicated in various health effects. We recently demonstrated that subacute oral exposure to DON significantly exacerbates symptoms of type 2 helper T-cell-mediated allergic diseases in a model. We aim to investigate the role of oral DON exposure in type 17 helper T-cell-mediated immunoreactive diseases using a mouse psoriasis model. Psoriasis was induced by the dermal administration of 5% imiquimod in female BALB/c mice. A standard rodent diet was supplemented with DON to achieve a final concentration of 0.3 ppm (1.5 μg/kg bw/day), which was administered daily for 14 days. Skin thickness, scratching behavior, and transepidermal water loss (TEWL) were continuously measured during imiquimod administration. Mice exposed to DON exhibited significant increases in skin thickness, TEWL, and scratching behavior. Histological evaluations revealed aggravated hyperplasia, neutrophil infiltration, and inflammatory cell accumulation in the dermis. Furthermore, DON exposure significantly increased the number of CD4+ helper T cells and CD11c+ MHC class II+ dendritic cells in the auricular lymph nodes, along with elevated TNF-α and IL-17 levels in stimulated T cells. The gene expression of IL-17 in skin tissue was also significantly up-regulated in DON-treated mice. Collectively, these findings suggest that oral exposure to DON aggravates symptoms in a mouse psoriasis model.